An Organic–Inorganic Hybrid Electrolyte as a Cathode Interlayer for Efficient Organic Solar Cells. (3rd March 2021) - Zhao, Chaowei; Zhang, Zhou; Han, Faming; Xia, Dongdong; Xiao, Chengyi; Fang, Jie; Zhang, Yuefeng; Wu, Binghui; You, Shengyong; Wu, Yonggang; Li, Weiwei
Abstract: An organic–inorganic hybrid electrolyte based on a cyclic Ti‐oxo cluster as the inorganic core and naphthalene‐based organic ammonium bromide salts as the electrolyte was developed with easy synthesis and low cost. The new hybrid electrolyte exhibits excellent solubility in methanol, aligned work function, good conductivity, and amorphous state in thin film, enabling its successful application as a cathode interlayer in organic solar cells with a high power conversion efficiency of 17.19 %. This work demonstrates that the hybrid electrolytes are a new kind of semiconductor, exhibiting promising applications in organic electronics. Abstract : An organic–inorganic hybrid electrolyte with aligned energy levels, self‐doping behavior, and improved electron mobility and conductivity was developed. It facilitates electron transport and boosts the power conversion efficiency of organic solar cells to 17.19 %.